Addressing diverse challenges in teaching reading comprehension: Voices among Indonesian university teachers - Budianto, Langgeng; Yuniar, Rendhi Fatrisna; Rohmana, Wahyu Indah Mala (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Many students struggle with reading comprehension due to limited vocabulary and lack of background knowledge, often leading to insufficient understanding of texts. While research has extensively explored reading comprehension at primary and secondary levels, challenges in higher education, particularly in Islamic-based institutions, remain underexamined. This study investigates the difficulties faced by Indonesian university teachers in teaching reading comprehension within such a context. Using a mixed-methods approach, the research combined qualitative data from non-participatory observations and semi-structured interviews with quantitative survey data. Participants included three English teachers teaching reading comprehension at a university in Malang, Indonesia, selected through purposeful sampling for their direct classroom engagement and ability to provide first-hand insights. Data analysis involved data reduction, data display, and drawing conclusions to identify recurring themes and patterns, combined with descriptive statistics to summarize survey results of the identified challenges. The findings reveal multifaceted challenges of teaching reading, stemming from both instructional and student-related factors, such as limited vocabulary mastery, low motivation, and inadequate resources. These findings emphasize the need for better professional development, resource management, and strategic intervention to support students and teachers. The study offers valuable insights for policymakers, educators, and researchers to improve instructional practices in Indonesian higher education.